A Comparative Evaluation of Solid-State Catalysts for Synthesis of Non-Ionic Surfactant Based Oleic Acid for Enhanced Oil Recovery (EOR) - Sampora, Yulianti; Sofyan, Muhammad Ihsan; Ghozali, muhammad; Triwulandari, Evi; Restu, Witta Kartika; Ndruru, Sun Theo Constan Lotebulo; Devy, Yenni Apriliany; Handayani, Annisa Fitriyah; Safitri, Gita Nur; Satria, Erza Eka (Universitas Jenderal Soedirman, 2025)
Abstract. The Enhanced Oil Recovery (EOR) process with chemical techniques carried out by injecting chemicals such as surfactants, can be an alternative to increase oil production, especially in old oil wells. This study investigated the best formulation of non-ionic surfactants based on the mole ratio of oleic acid and PEG-400 as well as catalyst types such as KOH and p-TSA 1%, which are used in surfactant synthesis to be able to increase oil production. The tests carried out are the value of acid, saponification, ester, and iodine, FTIR, NMR as well as a test of compatibility, phase behavior, and IFT. The results showed that the best formulation of ester polyethylene glycol oleate with reaction temperature conditions of 130oC was at a mole ratio of 1: 4 using a 1% p-TSA catalyst with a value of acid is 3,61 mg KOH/g, saponification is 144,12 mg KOH/g, ester is 140,51 mg KOH/g and iodine is 76,70 g I2/100 g. The compatibility tests and phase behavior show that this surfactant can be developed in chemical EOR with an IFT value of 2,6 x 10-1 mN/m. Keywords: Enhanced oil recovery, oleic acid, solid-state catalysts, synthesis